Building insulation board

By composited modified polystyrene particles and other materials in aluminate cement, combined with dual foaming technology, high-strength, low-density, flame-resistant building insulation boards were prepared, solving the problem of easy damage to existing insulation boards during temperature changes and structural deformation.

CN119638344APending Publication Date: 2025-03-18SHUIFA CONSTR & INSTALLATION ENG GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925316.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing building insulation panels are prone to damage when temperature changes and structural deformation, resulting in large-scale falloff and overall structure damage.

Method used

Lightweight, thermally insulated building insulation boards are prepared by double foaming technology using polystyrene particles compositely modified in aluminate cement, combined with acrylate and styrene copolymer powder and polypropylene fibers.

Benefits of technology

The overall strength and composite properties of the insulation board are improved, the combustibility is reduced, the structural strength and insulation effect of the insulation board are ensured, and damage caused by temperature changes and structural deformation is avoided.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a building insulation board, which comprises the following raw materials by mass: 90-100 parts of aluminate cement; 10 to 15 parts of polyphenyl particles; 1-3 parts of polypropylene fiber; 4-6 parts of a foaming agent; 3-5 parts of acrylate and styrene copolymerized rubber powder; 6-8 parts of phosphoric acid; and 2-4 parts of aluminum hydroxide. The mode that modified polyphenyl particles are compounded in aluminate cement is adopted, the flammability of the insulation board can be reduced, the compounding property of the polyphenyl particles in the whole system can be improved, the integrality of the whole system is enhanced through the acrylate and styrene copolymer rubber powder and the polypropylene fiber, the overall strength of the building insulation board is guaranteed, and the building insulation board is suitable for being used as a building insulation board. And the foaming agent plays a role in foaming, so that the aim of preparing the light and heat-insulating heat-insulating plate can be finally achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a building insulation board. Background Art

[0002] In order to improve the energy efficiency of buildings during use, insulation structures are generally set on the outside of the walls. The commonly used insulation structures are mainly set on the outside of the wall by bonding and other methods, and then external protective structures such as real stone paint are set on the outside of the insulation structure to ensure the protection of the insulation structure. This is mainly because the insulation boards currently used are generally foam types. During use, due to the difference between their own properties and the properties of the external real stone paint and the internal concrete, when the temperature changes, the structure is deformed, or partially damaged, it will cause large-scale damage to the insulation structure on the wall, followed by falling off, etc., and ultimately damage the overall structure. Summary of the invention

[0003] In order to solve the above problems, the present application proposes a building insulation board, comprising the following raw materials in parts by weight:

[0004] Aluminate cement: 90-100 parts;

[0005] Polystyrene particles: 10-15 parts;

[0006] Polypropylene fiber: 1-3 parts;

[0007] Foaming agent: 4-6 parts;

[0008] Acrylate and styrene copolymer powder: 3-5 parts;

[0009] Phosphoric acid: 6-8 parts;

[0010] Aluminum hydroxide: 2-4 parts. The present application adopts the method of compounding modified polystyrene particles in aluminate cement, which can reduce the flammability of the insulation board and improve the compositeness of the polystyrene particles in the whole system, while the acrylic ester and styrene copolymer powder and polypropylene fiber strengthen the integrity of the whole system and ensure the overall strength of the building insulation board, and the foaming agent plays a foaming role, and finally the purpose of preparing a lightweight and heat-insulating insulation board can be achieved.

[0011] Preferably, the foaming agent is sodium dodecyl sulfate and hydrogen peroxide, wherein the mass fraction of sodium dodecyl sulfate is 3-5 parts, and the rest is hydrogen peroxide, and the concentration of hydrogen peroxide is 20-30wt%; it also includes water, and the mass fraction of water is 40-50 parts. The present application adopts a double and unequal foaming method, which can maximize the structural strength formed by the outer layer material, that is, the outer layer material, and the low density and high thermal insulation of the inner layer material. When in use, the outer layer material layer can be used as an outer protective layer.

[0012] Preferably, the concentration of the phosphoric acid is 30-40 wt %.

[0013] Preferably, it is prepared as follows:

[0014] Polystyrene particle modification:

[0015] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0016] Material mixing:

[0017] The modified polystyrene particles, aluminate cement, polypropylene fibers, acrylic ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0018] Layered foaming:

[0019] Take out part of the base material, add a corresponding amount of hydrogen peroxide and part of water, and mix well to obtain the outer layer material;

[0020] The other parts of the basic materials, part of the water and sodium dodecyl sulfate are stirred thoroughly for not less than 1 hour to obtain the inner layer material;

[0021] A curing template is set up, and an outer layer of material is poured at the bottom of the curing template. Then, a mesh cloth layer is set up on the top of the outer layer of material, and then an inner layer of material is poured immediately to obtain an overall insulation layer.

[0022] Maintenance cutting:

[0023] The whole insulation layer is cured, and the formwork is removed after 3-4 days of curing, and the insulation board is obtained by cutting as required.

[0024] Preferably, several layers of mesh cloth are laid inside the outer layer material.

[0025] Preferably, the amount of the basic material in the outer layer material is 1 / 4-1 / 5 of the total amount of the basic material; the amount of water in the outer layer material is 1 / 4-1 / 5 of the total amount of water.

[0026] Preferably, the thickness of the outer layer material is 10-15 mm; the thickness of the inner layer material is 60-80 mm.

[0027] Preferably, the polyphenylene particles are modified in the following manner:

[0028] Adding polystyrene particles into phosphoric acid and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0029] Aluminum hydroxide is added to water with a mass of 2-3 times that of the aluminum hydroxide and stirred thoroughly to obtain an aluminum hydroxide suspension, and then the aluminum hydroxide suspension and the polyphenylene phosphate particle mixture are mixed thoroughly, and then the composite is dried to obtain modified polyphenylene particles;

[0030] The aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0031] Preferably, the composite is dried by spray drying.

[0032] Preferably, the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the addition speed is controlled so that the aluminum hydroxide suspension does not accumulate at the addition site. After the addition is completed, the stirring time is not less than 1 hour. The present application adopts the method of phosphoric acid impregnation and aluminum hydroxide compounding for polystyrene particles. On the one hand, the surface modification of polystyrene particles is completed to obtain the modified flame retardant effect. On the other hand, it improves its composite ability with other inorganic components to avoid its own aggregation, affecting the overall structural strength and the overall thermal insulation effect.

[0033] This application can bring the following beneficial effects:

[0034] 1. The present application adopts the method of compounding modified polystyrene particles in aluminate cement, which can reduce the flammability of the insulation board and improve the complexity of the polystyrene particles in the entire system, while the acrylic ester and styrene copolymer powder and polypropylene fiber strengthen the integrity of the overall system and ensure the overall strength of the building insulation board. The foaming agent plays a foaming role, and ultimately the purpose of preparing a lightweight and heat-insulating insulation board can be achieved.

[0035] 2. This application adopts a double, unequal foaming method, which can maximize the structural strength formed by the outer layer material and the low density and high thermal insulation of the inner layer material. When in use, the outer layer material layer can be used as an outer protective layer.

[0036] 3. The present application adopts the method of phosphoric acid impregnation and aluminum hydroxide compounding for polystyrene particles. On the one hand, it completes the surface modification of the polystyrene particles to obtain the modified flame retardant effect. On the other hand, it improves its composite ability with other inorganic components to avoid its own aggregation, affecting the overall structural strength and the overall thermal insulation effect. DETAILED DESCRIPTION

[0037] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0038] The present application discloses a building insulation board and a specific preparation method thereof, comprising the following raw materials in parts by weight:

[0039] Aluminate cement: 90-100 parts;

[0040] Polystyrene particles: 10-15 parts;

[0041] Polypropylene fiber: 1-3 parts;

[0042] Foaming agent: 4-6 parts;

[0043] Acrylate and styrene copolymer powder: 3-5 parts;

[0044] Phosphoric acid: 6-8 parts;

[0045] Aluminum hydroxide: 2-4 parts.

[0046] The foaming agent is sodium dodecyl sulfate and hydrogen peroxide, wherein the mass fraction of sodium dodecyl sulfate is 3-5 parts, and the rest is hydrogen peroxide, and the concentration of hydrogen peroxide is 20-30wt%; and water is also included, and the mass fraction of water is 40-50 parts.

[0047] The concentration of the phosphoric acid is 30-40 wt %.

[0048] During preparation, the following steps are followed:

[0049] S1. Polystyrene particle modification:

[0050] Modifying polystyrene particles by phosphoric acid (30-40 wt%) and aluminum hydroxide to obtain modified polystyrene particles;

[0051] Adding 10-15 parts of polystyrene particles to 6-8 parts of phosphoric acid and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0052] Add 2-4 parts of aluminum hydroxide to water 2-3 times the mass of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0053] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0054] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0055] S2. Material mixing:

[0056] The modified polystyrene particles, 90-100 parts of aluminate cement, 1-3 parts of polypropylene fibers, 3-5 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0057] S3. Layered foaming:

[0058] Take out 1 / 4-1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20-30wt%) and 1 / 4-1 / 5 of 40-50 parts of water, and mix well to obtain the outer layer material;

[0059] Mix the other parts of the base material, the other parts of the water and 3-5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0060] Set up a curing template, pour the outer material at the bottom of the curing template, lay several layers of mesh cloth inside the outer material to form an outer material layer of 10-15mm, then set a mesh cloth layer on the top of the outer material, and then immediately pour the inner material to form an inner material layer of 60-80mm, and finally obtain the overall insulation layer;

[0061] S4. Maintenance cutting:

[0062] The whole insulation layer is cured, and the formwork is removed after 3-4 days of curing, and the insulation board is obtained by cutting according to the size requirements.

[0063] In order to characterize the effectiveness of this application, the following examples are made:

[0064] Embodiment 1:

[0065] S101. Polystyrene particle modification:

[0066] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0067] Adding 10 parts of polystyrene particles to 6 parts of phosphoric acid (40 wt%) and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0068] Add 2 parts of aluminum hydroxide into water with a mass twice that of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0069] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0070] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0071] S102.Material mixing:

[0072] The modified polystyrene particles, 90 parts of aluminate cement, 1 part of polypropylene fiber, 3 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0073] S103. Layered foaming:

[0074] Take out 1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%) and 10 parts of water, and mix well to obtain the outer layer material;

[0075] Mix the other basic materials, 30 parts of water and 5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0076] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 10 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 60 mm, and finally the overall insulation layer is obtained;

[0077] S104. Maintenance cutting:

[0078] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 1 of 200mm*200mm is cut according to the size requirements.

[0079] The properties of insulation board No. 1 were tested, and its thermal conductivity (25°C) was 0.0271W / (mK), its flexural strength was 0.27MPa, and its combustion performance was A1 grade.

[0080] Embodiment 2:

[0081] S201. Polystyrene particle modification:

[0082] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0083] Add 15 parts of polystyrene particles to 8 parts of phosphoric acid (30 wt%) and mix them thoroughly to obtain a phosphate polystyrene particle mixture;

[0084] Add 4 parts of aluminum hydroxide into water 3 times the mass of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0085] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0086] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0087] S202.Material mixing:

[0088] The modified polystyrene particles, 100 parts of aluminate cement, 3 parts of polypropylene fibers, 5 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0089] S203. Layered foaming:

[0090] Take out 1 / 4 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 30wt%) and 12.5 parts of water, and mix well to obtain the outer layer material;

[0091] Mix the other basic materials, 37.5 parts of water and 3 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0092] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 15 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 80 mm, and finally the overall insulation layer is obtained;

[0093] S204. Maintenance cutting:

[0094] The whole insulation layer is cured, and the formwork is removed after 4 days of curing. The insulation board No. 2 of 200mm*200mm is cut according to the size requirements.

[0095] The properties of insulation board No. 2 were tested, and its thermal conductivity (25°C) was 0.0302W / (mK), its flexural strength was 0.29MPa, and its combustion performance was A1 grade.

[0096] Comparative Example 1:

[0097] S301.Material mixing:

[0098] 10 parts of polystyrene particles, 6 parts of phosphoric acid (40 wt%), 2 parts of aluminum hydroxide, 90 parts of aluminate cement, 1 part of polypropylene fiber, 3 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a base material;

[0099] S302. Layered foaming:

[0100] Take out 1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%) and 10 parts of water, and mix well to obtain the outer layer material;

[0101] Mix the other basic materials, 30 parts of water and 5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0102] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 10 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 60 mm, and finally the overall insulation layer is obtained;

[0103] S303. Maintenance cutting:

[0104] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 3 with a size of 200mm*200mm is cut according to the size requirements.

[0105] The properties of insulation board No. 3 were tested, and its thermal conductivity (25°C) was 0.0318W / (mK), its flexural strength was 0.25MPa, and its combustion performance was A2 level.

[0106] Comparative Example 2:

[0107] S401. Polystyrene particle modification:

[0108] Modifying polystyrene particles by phosphoric acid to obtain modified polystyrene particles;

[0109] Adding 10 parts of polystyrene particles to 6 parts of phosphoric acid (40 wt%) and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0110] The polyphenyl phosphate particle mixture is spray-dried to obtain modified polyphenyl particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0111] S402.Material mixing:

[0112] The modified polystyrene particles, 90 parts of aluminate cement, 1 part of polypropylene fiber, 3 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0113] S403. Layered foaming:

[0114] Take out 1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%) and 10 parts of water, and mix well to obtain the outer layer material;

[0115] Mix the other basic materials, 30 parts of water and 5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0116] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 10 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 60 mm, and finally the overall insulation layer is obtained;

[0117] S404. Maintenance cutting:

[0118] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 4 with a size of 200mm*200mm is cut according to the size requirements.

[0119] The properties of the No. 4 insulation board were tested, and its thermal conductivity (25°C) was found to be 0.0344W / (mK), its flexural strength was 0.26MPa, and its combustion performance was A2 level.

[0120] Comparative Example 3:

[0121] S501. Polystyrene particle modification:

[0122] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0123] Adding 10 parts of polystyrene particles to 6 parts of phosphoric acid (40 wt%) and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0124] Add 2 parts of aluminum hydroxide into water with a mass twice that of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0125] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0126] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0127] S502.Material mixing:

[0128] The modified polystyrene particles, 90 parts of silicate cement, 1 part of polypropylene fiber, 3 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a base material;

[0129] S503. Layered foaming:

[0130] Take out 1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%) and 10 parts of water, and mix well to obtain the outer layer material;

[0131] Mix the other basic materials, 30 parts of water and 5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0132] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 10 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 60 mm, and finally the overall insulation layer is obtained;

[0133] S504. Maintenance cutting:

[0134] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 5 with a size of 200mm*200mm is cut according to the size requirements.

[0135] For the No. 5 insulation board, its thermal conductivity (25°C) was tested to be 0.0285W / (mK), its flexural strength was 0.22MPa, and its combustion performance was A1 grade.

[0136] Comparative Example 4:

[0137] S601. Polystyrene particle modification:

[0138] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0139] Adding 10 parts of polystyrene particles to 6 parts of phosphoric acid (40 wt%) and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0140] Add 2 parts of aluminum hydroxide into water with a mass twice that of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0141] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0142] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0143] S602.Material mixing:

[0144] The modified polystyrene particles, 90 parts of aluminate cement and 1 part of polypropylene fiber are dry-mixed to obtain a base material;

[0145] S603. Layered foaming:

[0146] Take out 1 / 5 of the base material by weight, add 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%) and 10 parts of water, and mix well to obtain the outer layer material;

[0147] Mix the other basic materials, 30 parts of water and 5 parts of sodium dodecyl sulfate, and then stir them thoroughly for not less than 1 hour to obtain the inner layer material;

[0148] A curing template is set up, and the outer layer material is poured at the bottom of the curing template. Several layers of mesh cloth are laid inside the outer layer material to form an outer layer material layer of 10 mm, and then a mesh cloth layer is set on the top of the outer layer material, and then the inner layer material is immediately poured to form an inner layer material layer of 60 mm, and finally the overall insulation layer is obtained;

[0149] S604. Maintenance cutting:

[0150] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 6 of 200mm*200mm is cut according to the size requirements.

[0151] For the No. 6 insulation board, its thermal conductivity (25°C) was tested to be 0.0322W / (mK), its flexural strength was 0.23MPa, and its combustion performance was A1 grade.

[0152] Comparative Example 5:

[0153] S701. Polystyrene particle modification:

[0154] Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles;

[0155] Adding 10 parts of polystyrene particles to 6 parts of phosphoric acid (40 wt%) and mixing them thoroughly to obtain a phosphate polystyrene particle mixture;

[0156] Add 2 parts of aluminum hydroxide into water with a mass twice that of the aluminum hydroxide and stir thoroughly to obtain an aluminum hydroxide suspension;

[0157] Then, the aluminum hydroxide suspension and the polystyrene phosphate particle mixture are fully mixed, and the aluminum hydroxide suspension is added dropwise to the rapidly stirred mixture of phosphoric acid and polystyrene particles, and the adding speed is controlled so that the aluminum hydroxide suspension is not accumulated at the adding part;

[0158] After the addition is completed, the stirring time is not less than 1 hour; the composite is then spray-dried to obtain modified polyphenylene particles; the aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

[0159] S702.Material mixing:

[0160] The modified polystyrene particles, 90 parts of aluminate cement, 1 part of polypropylene fiber, 3 parts of acrylic acid ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material;

[0161] S703. Foaming into board:

[0162] Mix the base material, 1 part of hydrogen peroxide (hydrogen peroxide concentration is 20wt%), 40 parts of water and 5 parts of sodium dodecyl sulfate, and then stir thoroughly for not less than 1 hour;

[0163] Set up a curing template, pour materials inside the curing template to form a 70mm material layer, and finally obtain an overall insulation layer;

[0164] S704. Maintenance cutting:

[0165] The whole insulation layer is cured, and the mold is removed after 3 days of curing. The insulation board No. 7 with a size of 200mm*200mm is cut according to the size requirements.

[0166] The properties of the No. 7 insulation board were tested, and its thermal conductivity (25°C) was found to be 0.0415 W / (mK), its flexural strength was 0.26 MPa, and its combustion performance was A1 grade.

[0167] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A building insulation board, characterized in that: Including the following raw materials by mass: Aluminate cement: 90-100 parts; Polystyrene particles: 10-15 parts; Polypropylene fiber: 1-3 parts; Foaming agent: 4-6 parts; Acrylate and styrene copolymer powder: 3-5 parts; Phosphoric acid: 6-8 parts; Aluminum hydroxide: 2-4 parts.

2. A building insulation board as claimed in claim 1, characterized in that: The foaming agent is sodium dodecyl sulfate and hydrogen peroxide, wherein the mass fraction of sodium dodecyl sulfate is 3-5 parts, and the rest is hydrogen peroxide, and the concentration of hydrogen peroxide is 20-30wt%; and water is also included, and the mass fraction of water is 40-50 parts.

3. A building insulation board as claimed in claim 1, characterized in that: The concentration of the phosphoric acid is 30-40 wt %.

4. A building insulation board as claimed in claim 2, characterized in that: Prepared as follows: Polystyrene particle modification: Modifying polystyrene particles by phosphoric acid and aluminum hydroxide to obtain modified polystyrene particles; Material mixing: The modified polystyrene particles, aluminate cement, polypropylene fibers, acrylic ester and styrene copolymer rubber powder are dry-mixed to obtain a basic material; Layered foaming: Take out part of the base material, add a corresponding amount of hydrogen peroxide and part of water, and mix well to obtain the outer layer material; The other parts of the basic materials, part of the water and sodium dodecyl sulfate are stirred thoroughly for not less than 1 hour to obtain the inner layer material; A curing template is set up, and an outer layer of material is poured at the bottom of the curing template. Then, a mesh cloth layer is set up on the top of the outer layer of material, and then an inner layer of material is poured immediately to obtain an overall insulation layer. Maintenance cutting: The whole insulation layer is cured, and the formwork is removed after 3-4 days of curing, and the insulation board is obtained by cutting as required.

5. A building insulation board as claimed in claim 4, characterized in that: Several layers of mesh cloth are laid inside the outer material.

6. A building insulation board as claimed in claim 4, characterized in that: The amount of the basic material in the outer layer material is 1 / 4-1 / 5 of the total amount of the basic material; the amount of water in the outer layer material is 1 / 4-1 / 5 of the total amount of water.

7. A building insulation board as claimed in claim 4, characterized in that: The thickness of the outer layer material is 10-15 mm; the thickness of the inner layer material is 60-80 mm.

8. A building insulation board as claimed in claim 4, characterized in that: The polyphenylene particles are modified as follows: Adding polystyrene particles into phosphoric acid and mixing them thoroughly to obtain a phosphate polystyrene particle mixture; Aluminum hydroxide is added to water with a mass of 2-3 times that of the aluminum hydroxide and stirred thoroughly to obtain an aluminum hydroxide suspension, and then the aluminum hydroxide suspension and the polyphenylene phosphate particle mixture are mixed thoroughly, and then the composite is dried to obtain modified polyphenylene particles; The aluminum hydroxide is nano aluminum hydroxide with a particle size of 10-50 nm.

9. A building insulation board as claimed in claim 8, characterized in that: The composite is dried by spray drying.

10. A building insulation board as claimed in claim 8, characterized in that: Add the aluminum hydroxide suspension dropwise into the rapidly stirred mixture of phosphoric acid and polystyrene particles, controlling the adding speed so that no aluminum hydroxide suspension accumulates at the adding site. After the addition is completed, the stirring time should be no less than 1 hour.